Establishment and evaluation of a method for measuring ornithine transcarbamylase activity in micro blood of neonates - Zhilei Zhang; Xin Wang; Jingjing Zhang; Xianwei Guan; Yanyun Wang; Dongyang Hong; Yahong Li; Peiying Yang; Yun Sun; Tao Jiang (Orphanet Journal of Rare Diseases)
Abstract Background Ornithine transcarbamylase deficiency exhibits a high degree of clinical heterogeneity, making its screening and classification challenging in some instances. In this study, we first established a simple and stable method for testing ornithine transcarbamylase activity using micro blood from newborns, rather than relying on venous blood. Methods The activity of ornithine transcarbamylase was assessed by measuring the concentration of citrulline produced in the reaction with carbamoyl phosphate and ornithine, using serum, plasma or micro blood. Correlation analysis was evaluated using Sangerbox Tools. The Receiver Operating Characteristic curve was used in SPSS Statistics 17.0 to evaluate the diagnostic efficiency of Ornithine transcarbamylase deficiency. Results A strong linear relationship was observed between ornithine transcarbamylase activity and both micro blood volume and reaction time (R2 = 0.9793, 0.9922 respectively). The intra-coefficient variation and inter-coefficient variation were 11% and 12.5% with a 1-h reaction time, and 6.77% and 9.58% with a 3-h reaction time, respectively. And the inter-coefficient variation was lower than the most widely used colorimetry method (5.1–21.1%). The Limit of Blank was 0.57 nmol/mL/h. The reference interval for normal newborn population is greater than or equal to 39.6 nmol/mL/h. Notably, the method exhibited a 100% sensitivity, surpassing the sensitivity of colorimetry method (94.3%), along with and a specificity of 96.9% for diagnosing ornithine transcarbamylase deficiency. Conclusions We pioneered a method for testing OTC activity that normally carried on venous blood can be effectively performed on microblood heel samples. Meanwhile, our method presents a simpler, more stable and reproducible approach compared to colorimetry.